Effects of telmisartan on vascular endothelial function, inflammation and insulin resistance in patients with coronary heart disease and diabetes mellitus - Chen, Tao (Exp Ther Med, 2018)
The aim of the present study was to investigate the effects of telmisartan on vascular endothelial functions, inflammatory factors and insulin resistance of coronary heart disease patients complicated with diabetes mellitus. In total, 80 coronary heart disease patients complicated with type 2 diabetes mellitus, admitted and treated in the Zhangqiu Hospital from January 2016 to March 2017 were enrolled in the study. Each patient was randomly assigned to an observation (n=40) or a control group (n=40) using a random number table. Conventional symptomatic and supporting therapies were administered to all the patients in the two groups for 12 consecutive weeks, while additional telmisartan was given only to patients in the observation group. Markers of glucose metabolism, vascular endothelial function and inflammation were determined before and after intervention, to compare averages between groups. Results showed the levels of fasting blood glucose and blood glucose in the observation group were significantly lower than those in the control group (p<0.05) after 4 weeks of treatment. The levels of HOMA-IR in the observation group were clearly improved compared to those in the control group during the same period (p<0.05). After the intervention, the levels of FINS and HOMA-IR in the observation group improved significantly more compared with those in the control group (p<0.05), while the levels of tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6) and C-reactive protein (CRP) were much lower than those in the control group (p<0.05). Furthermore, at the 4th, 8th and 12th week after starting the treatment, the vascular endothelin (ET) levels in the observation group were significantly lower than those in the control group (p<0.05). In addition, the brachial artery diameters in the basal state were significantly larger than those in the control group (p<0.05) for the same time-points. Coronary heart disease patients complicated with diabetes mellitus whose treatment includes telmisartan can better regulate their blood glucose, reduce the insulin resistance and body inflammatory responses and improve their vascular endothelial functions.